In vitro testing of honey quality and biological functionality: underestimated elements in the clinical testing of honey - Majtan, Juraj (Frontiers in Nutrition, 2024)
Honey is an attractive functional food that often becomes a subject of clinical studies on the treatment of diverse diseases. However, the clinical efficacy of honey is rather controversial due, at least in part, to its variable composition and botanical origin as well as thermal processing or improper storage conditions. This review addresses the importance of honey quality standards and in vitro testing of the biological properties of honey prior to performing clinical studies, which can have a great impact on clinical outcomes. It focused on recently performed meta-analyses and systematic reviews where honey was used in the management of various disorders including respiratory tract infections, and metabolic and cardiometabolic diseases, with the goal of characterising the honeys used in clinical studies. In addition, it provides recommendations for the use and storage of honey for clinical testing. The vast majority of clinical studies included in meta-analyses do not provide any information about honey quality parameters. In fact, indicators of thermal damage or prolonged storage of honey were analysed only in one clinical study. This observation highlights on the alarming status of honey quality in clinical studies. Furthermore, in vitro biological properties of the analysed honeys were assessed in two clinical studies. Therefore, this review strongly advocates the clinical use of only fully characterized honey samples of known botanical origin with proven in vitro biological functionality and no or minimal thermal processing.